The historical framework of the Lebanese National Pact of 1943 and its role in promoting sectarianism, according to the visions and analyses of the Egyptian International Politics magazine. - Hussein Sahlih Shana , Assist. Lect.; Rahim Kazim Muhammad, Prof. Dr. (Wasit Journal for Human Sciences, 2025)
The Lebanese National Pact of 1943 played a pivotal and fundamental role in consolidating sectarianism in Lebanon. Despite being an unwritten pact, it established the principle of partisan quotas based on religious and ethnic sectarian principles for power-sharing. It was agreed that the presidency would be for Christians, the prime minister ship for Sunni Muslims, and the presidency for Parliament for Shiite Muslims. This agreement was reached between Lebanese leaders representing the sects, especially Bechara El Khoury, a Christian, and Riad El Solh, a Muslim. However, it did not resolve the problem; rather, it deepened sectarian divisions and fueled an atmosphere of rivalry and competition between the sects over the gains and spoils that they considered their legitimate right. Over time, the The feeling of marginalization among the poor and small sects, coupled with the absence of necessary political and social reforms, increased sectarian tension in the country. This fragile sectarian class structure, along with the external support it received from regional and international sources, had a significant impact on the outbreak of civil war on April 13, 1975. The sects transformed into militias. Armed groups engaged in a war, which confirmed the fragility of the political system in Lebanon, which was a product of the National Pact of 1943.
Keywords: : Charter - Lebanon - Sectarianism - War - Militias - Quotas